Assessing Forest Vitality and Forest Structure Using 3D Data: A Case Study From the Hainich National Park, Germany - Heidenreich, Marius G.; Seidel, Dominik (Frontiers in Forests and Global Change, 2022)
The adaptation of forest management to changing environmental conditions due to climate change relies on information on the current forest and tree vitality. In common practice, the percentage of crown defoliation is used as proxy for tree vitality, an approach that has several drawbacks. By performing laser scanning on a forest plot in the Hainich National Park we tested a new approach to quantifying tree vitality. Based on the difference in structural complexity measured between summer and winter, assessed via the box-dimension, the new approach provides an objective and reproducible method that does not only allow the quantification of the defoliation, but also includes the effects of branch diebacks. Additionally, we assessed the change in box-dimension and branch lengths between 2013 and 2021 and studied the overall structural development of the trees to analyze the alteration of their vitality. On average, we found a decrease in overall structural complexity, as well as in branch lengths for most trees in the investigated forest. Further, the mean difference in box-dimension (summer minus winter) decreased with ascending vitality class. We conclude that the vitality of the trees was negatively affected over the period of eight years, and we argue the newly proposed method based on the box-dimension holds potential to be used as a measure for tree vitality in deciduous forests.